Thromboangiitis Obliterans Treated with Individualized Homeopathic Medicine: A Case Report - Mathur, Mohit (Homœopathic Links, 2025)
Thromboangiitis obliterans is a nonatherosclerotic, inflammatory disease affecting the small- and medium-sized arteries and veins of the extremities. Its prevalence among patients with peripheral arterial disease varies from 0.5 to 5.6% in Western Europe and 45 to 63% in India. It frequently affects vessels of the upper and lower extremities, where it causes migratory thrombophlebitis and arterial insufficiency. So far, there is no reported study evaluating individualized homeopathic intervention in thromboangiitis obliterans in peer-reviewed journals. The following case study presents a case of small thromboangiitis obliterans presenting with rest pain and ischemic gangrene in the left foot toe. The case was prescribed Carbo Animalis based on local modalities and prominent veins on the affected limb. There was marked improvement in rest pain and full recovery of gangrene, thus avoiding the need for amputation. The modified Naranjo score was +10, which indicated a definite causal attribution. This case study suggests that individualized homeopathic treatment can be helpful in thromboangiitis obliterans with no-option critical limb ischemia. The findings of this case study merit a more rigorous trial to test the action of Carbo Animalis in cases of peripheral arterial diseases.
Keywords: Buerger's disease; Carbo Animalis; individualized homeopathy; ischemic; gangrene; thromboangiitis obliterans